Habitat damage, marine reserves, and the value of spatial management. Issue 5 (1st July 2013) - Moeller, Holly V.; Neubert, Michael G.
Abstract : The biological benefits of marine reserves have garnered favor in the conservation community, but "no‐take" reserve implementation is complicated by the economic interests of fishery stakeholders. There are now a number of studies examining the conditions under which marine reserves can provide both economic and ecological benefits. A potentially important reality of fishing that these studies overlook is that fishing can damage the habitat of the target stock. Here, we construct an equilibrium bioeconomic model that incorporates this habitat damage and show that the designation of marine reserves, coupled with the implementation of a tax on fishing effort, becomes both biologically and economically favorable as habitat sensitivity increases. We also study the effects of varied degrees of spatial control on fisheries management. Together, our results provide further evidence for the potential monetary and biological value of spatial management, and the possibility of a mutually beneficial resolution to the fisherman–conservationist marine reserve designation dilemma.